Recent Advances in Magnetic-Nanomaterial-Based Mechanotransduction for Cell Fate Regulation - Wu, Congyu (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.